In defense of the Republic. Saragossan anticlericalism through the press: Vida Nueva and El Radical in the first biennium - Zugasti, Ricardo (Historia y Comunicación Social, 2023)
This paper analyses the anticlerical discourse in the first two years of the Spanish Second Republic by examining two weekly newspapers from Saragossa: Vida Nueva, the official publication of the Socialist Party, and El Radical, edited by the youth wing of the Radical Republican Party. Specifically, the study covers what was published during the period of greatest effervescence of the religious conflict during the Second Republic, from the beginning of the parliamentary processing of the Law of Confessions and Religious Congregations until the Catholic mobilization which led to its approval (February-June 1933). The conclusions reveal that, in addition to other similarities and differences, both newspapers formed a common front in which the anticlerical discourse sought to mobilize readers in defense of the Republic.